2019
DOI: 10.1308/rcsann.2018.0170
|View full text |Cite
|
Sign up to set email alerts
|

Suture choice to reduce occurrence of surgical site infection, hernia, wound dehiscence and sinus/fistula: a network meta-analysis

Abstract: Background There are many options and little guiding evidence when choosing suture types with which to close the abdominal wall fascia. This network meta-analysis investigated the effect of suture materials on surgical site infection, hernia, wound dehiscence and sinus/fistula occurrence after abdominal surgery. The aim was to provide clarity on whether previous recommendations on suture choice could be followed with confidence. Methods and methods In February 2017, the Cochrane Central Register of Controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
8
0
3
Order By: Relevance
“…The incidence of incisional hernias that can be attributed to a certain suture type has been subject to fierce discussion in the surgical literature and was summed up by a recently published Cochrane review. The authors could not draw an evidence-based conclusion with regard to the most suitable suture materials which prevents all adverse events most effectively [ 13 ]. In our cohort, we currently do not provide any data on incisional hernias but further follow-up will clarify that issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of incisional hernias that can be attributed to a certain suture type has been subject to fierce discussion in the surgical literature and was summed up by a recently published Cochrane review. The authors could not draw an evidence-based conclusion with regard to the most suitable suture materials which prevents all adverse events most effectively [ 13 ]. In our cohort, we currently do not provide any data on incisional hernias but further follow-up will clarify that issue.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple studies on the best modalities of fascial closure after elective abdominal surgery procedures, comparing continuous to interrupted or absorbable to non-absorbable sutures. In the end, no significant differences have been found with regard to burst abdomen or incisional hernia in meta-analyses [ 12 , 13 ]. Generally, the risk of incisional hernia after abdominal surgery ranges from 12 to 25% [ 1 , 14 ] and reaches incidences as high as 83% after burst abdomen [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This guideline recommended the avoidance of fast-absorbable sutures and suggested the use of a slowly-absorbable monofilament sutures. On the other hand, it was reported that nylon sutures reduced the incisional hernia rate compared with both fast-absorbable and slowlyabsorbable sutures [17]. The best suture material for preventing incisional hernia remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…J. Morphol., 37(3):1073-1078, 2019 SUMMARY: Considering the advances in research that relate honey therapeutic effects in wound healing process, the present investigation aimed to evaluate and compare qualitatively, through morphological analysis, the local tissue response between conventional suture with Ulmoplus ® and without Ulmoplus ® in the closure of the rabbit skin incision. We used 10 adult rabbits, divided into group S (suture) and group S + U (suture plus Ulmoplus®).…”
Section: Espín L; Vásquez B; Schencke C and Del Sol M Comparisomentioning
confidence: 99%